Risk factors of stroke in coastal villages of Uttara Kannada district, Karnataka, India: a case control study - Jacob, George P.; Kulkarni, Muralidhar M. (International Journal Of Community Medicine And Public Health, 2017)
Background: The prevalence of stroke was reportedly higher in four coastal villages as compared to the neighbouring villages. Hence the study was conducted to identify the risk factors for stroke cases in the four villages of Mavinakurve Gram Panchayath, Bhatkal Taluk, Karnataka, India. Methods: 53 stroke patients were compared with 106 age and locality matched controls. Data was obtained using a predesigned, pretested questionnaire for socio-demographic variables, sources of water, palm oil and milk powder consumption, smoking and alcohol usage, stress score, history of hypertension, BMI and Waist Hip ratio. The data was entered in the SPSS version 15.0 and analysed. Results were expressed as proportions. Associations were analyzed using Chi-square test. A p-value less than 0.05 was considered significant. Results: Most of the cases (53%) and controls (45%) belonged to the age group of 60-69 years. 62.2% of the cases were males and 37.8% were females. 45.3% of the cases and 34.0% of the controls were involved in fishing. 15% of the cases and 2.8% of the controls had high stress. Statistically significant association was found between high stress and stroke. 86.8% of cases and 72.6% of controls were hypertensive (p value of 0.04). Conclusions: The prevalence of stroke in this area is higher than the state/national average. Hypertension and stress are important risk factors for stroke. Periodic screening for early detection of hypertension, health education, appropriate lifestyle modification and prompt treatment for hypertension are very important.